Understanding dietary carbohydrates in black soldier fly larvae treatment of organic waste in the circular economy. (1st January 2022) - Cohn, Zachary; Latty, Tanya; Abbas, Ali
Highlights: Galactose, xylose and arabinose additives reduced performance of BSFL treatment. Xylan reduced bioconversion and waste conversion efficiency. BSFL fat content was increased by wheat starch and decreased by galactose and xylan. Fatty acid profiles were largely unaffected by carbohydrate treatments. Abstract: Black soldier fly larvae (BSFL) treatment is promising for organic waste valorisation in the circular economy; however, waste variability impacts the process performance and quality of produced larvae. Specifically, variation in the carbohydrate profile of treated wastes has been suggested to have a significant impact on BSFL treatment performance and quality of produced larvae, with particular carbohydrates either positively or negatively influencing these variables. This study examines the hypothesis that the types of carbohydrates within the substrate can have significant influence on larval survival, waste reduction, bioconversion, and waste conversion efficiency, as well as the crude lipid content and fatty acid profiles of the produced larvae. The carbohydrates explored were D glucose, sucrose, D (−) fructose, corn and wheat starch, D (+) galactose, D (+) mannose, D (+) xylose, D (−) arabinose and xylan from beechwood. Young larvae were grown for 9 days on chicken feed-based diets containing various carbohydrate additives each at 20 dry mass %. Treatments containing hemicellulose constituents galactose and arabinose produced the most adverse effects on process performance relative to the benchmark. Xylan was significantly detrimental to bioconversion (−14.7 ± 3.8%) and waste conversion efficiencies (−19.0 ± 4.4%). There were minimal significant effects on performance from mono- and di-saccharides and starch additives. Larvae crude lipid contents were significantly increased by wheat starch (+12.6 ± 3.0%) and decreased by galactose (−15.0 ± 1.4%) and xylan additives (−27.5 ± 3.4%), however fatty acid profiles were largely unaffected and were dominated by lauric acid. These results indicate that despite an otherwise balanced and nutritious substrate, the carbohydrate profile of organic waste should be an important consideration in BSFL treatment when ensuring process performance and larval lipid contents. The consequences of these results for BSFL treatment of real wastes are discussed. Large scale treatment facilities should formulate substrates accordingly and identify methods to mitigate the anti-nutritional effects of poor carbohydrate profiles, particularly those high in hemicelluloses and their constituents.